Severe Acute Respiratory Syndrome Coronavirus-2 and Tuberculosis Coinfection: Double Trouble - Abhijeet Singh; Ayush Gupta; Kamanasish Das (Indian Journal of Medical Specialities)
The ongoing pandemic of novel coronavirus disease 2019 (COVID-19) has received worldwide attention by becoming a major global health threat. We encountered one case with COVID-19 and tuberculosis (TB) coinfection, which has not been frequently reported. A 76-year-old female presented with acute respiratory symptoms superimposed on chronic symptoms, suggestive to have pneumonia. Oropharyngeal throat swab sample for COVID-19 was positive as detected by real-time reverse transcriptase–polymerase chain reaction assay. GeneXpert Ultra detected Mycobacterium tuberculosis complex with rifampicin resistance indeterminate. The patient was treated with appropriate management. Clinicians should suspect coinfection with TB during the ongoing pandemic of COVID-19 as therapeutic strategies need to be determined timely to improve outcomes and prevent transmission in the community.